Is the optical conductivity of heavy fermion strange metals Planckian? - Li, Xinwei; Kono, Junichiro; Si, Qimiao; Paschen, Silke (Frontiers in Electronic Materials, 2023)
Strange metal behavior appears across a variety of condensed matter settings and beyond, and achieving a universal understanding is an exciting prospect. The beyond-Landau quantum criticality of Kondo destruction has had considerable success in describing the behavior of strange metal heavy fermion compounds, and there is some evidence that the associated partial localization-delocalization nature can be generalized to diverse materials classes. Other potential overarching principles at play are also being explored. An intriguing proposal is that Planckian scattering, with a rate of $k_{\rm B}T/\hbar$, leads to the linear temperature dependence of the (dc) electrical resistivity, which is a hallmark of strange metal behavior. Here we extend a previously introduced analysis scheme based on the Drude description of the dc resistivity to optical conductivity data. When they are well described by a simple (ac) Drude model, the scattering rate can be directly extracted. This avoids the need to determine the ratio of charge carrier concentration to effective mass, which has complicated previous analyses based on the dc resistivity. However, we point out that strange metals typically exhibit strong deviations from Drude behavior, as exemplified by the ``extreme'' strange metal YbRh$_2$Si$_2$. This calls for alternative approaches, and we point to the power of strange metal dynamical (energy-over-temperature) scaling analyses for the inelastic part of the optical conductivity. If such scaling extends to the low-frequency limit, a strange metal relaxation rate can be estimated, and may ultimately be used to test whether strange metals relax in a Planckian manner.